Effects of Entrepreneurial Leadership and Innovation Capacity on Employee Productivity and its Implication on Business Performance (Survey at some Supermarket at Cirebon City) - Hikmat, Hikmat; Dewi, Maya Puspita; Winanti, Marliana B (Jurnal Soshum Insentif, 2024)
This paper’s objectives are to know the influence of entrepreneurial leadership and innovation capacity on employee productivity and its implication on business performance. The method used is quantitative research implemented as a survey on several Supermarket. The data is analyzed using path analysis and mediation process. Research findings: First, entrepreneurial leadership and innovation capacity affect significantly employee productivity simultaneously. Second, entrepreneurial leadership affects employee productivity significantly. Third, innovation capacity affects employee productivity significantly. Fourth, employee productivity affects business performance significantly. Fifth, entrepreneurial leadership affects significantly on business performance as mediated by employee productivity. Sixth, Innovation Capacity affects significantly on business performance as mediated by employee productivity